Understanding Corruption in Organizations – Development and Empirical Assessment of an Action Model - Rabl, Tanja (Journal of business ethics, 2008)
Despite a strong sensitization to the corruption problem and a large body of interdisciplinary research, scientists have only rarely investigated which motivational, volitional, emotional, and cognitive components make decision makers in companies act corruptly. Thus, we examined how their interrelation leads to corruption by proposing an action model. We tested the model using a business simulation game with students as participants. Results of the PLS structural equation modeling showed that both an attitude and subjective norm favoring corruption led to a desire to act corruptly. Given high perceived behavioral control, this desire was transformed into an intention that finally resulted in corrupt action. Components related to general private and professional goals did not allow for any prediction. Based on these results, we discuss preventative measures and methods for combating intra- and inter-organizational corruption.